Pengenalan APOCIL (Apoteker Cilik) dan Edukasi Pentingnya Vitamin pada Anak di SDN Badurame Turi Lamongan - Irma Susanti; Tusamma Salsabiila; Novely Dwita Ramadhani; M. Muflih Zaki Al-Hadi; Annisa Ariantika; Gharizah Raisa Aqila; Sintya Shafa Qotrunnida (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The role of pharmacists is very important in providing education about medicines, especially vitamins. The introduction of vitamins at elementary school level is one of the duties of a pharmacist. This service was carried out at SDN Badurame with the theme